Die Wundersame Welt der Waschkraft - Schmid, Hans-Christian (Germany : 23/5 Filmproduktion, 2009)
Outside of Germany, labor is cheaper and regulations are less strict. This is the space where business can flourish: a company takes dirty laundry from German hotels to Poland - and brings it back clean the very next day. But over and beyond this capital venture there remains the harsh reality of the everyday life of the hard-working Polish laundrywomen. While Beata struggles to raise her three children on her meager salary, Monika reminisces about her unrealized childhood dreams of becoming a doctor, and is compelled to watch her teenage daughter Marta gradually follow in her footsteps.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films